Riba in Islamic Economics and Finance: A Review - Lina Marlina; Aisyah As Salafiyah; Ahlis Fatoni; Nurismalatri; Purnama Putra (SMART Insight, 2023)
Islam, Judaism, and Christianity prohibit Riba from economic and finance. The firm refusal of the practice of riba is because it negatively affects society, spiritual morals, social life, and the economic sector. This study aims to find out the development map and trend of riba published in Islamic economics and finance. The data analyzed were more than 169 research publications indexed by Scopus. The export data is then processed and analyzed using R Biblioshiny software to determine the bibliometric map of the development of riba. The result shows that the number of publications on the development of riba in Islamic economics and finance research increases continuously. This study provides a comprehensive explanation of usury and finds that usury negatively impacts both spiritually, socially and economically. This study is a comprehensive study that discusses the theme of redefining riba in bibliometric analysis.